The Relationship between Psychological Capital and Subjective Well-Being among Boarding School Adolescents - Yossie Susanti Eka Putri; Ice Yulia Wardani; Dian Fitria; Mahraniy; Pichitra Lekdamrongkul (Journal Of Nursing Practice, 2025)
Background: Psychological capital (Psycap), encapsulates positive mental attributes such as hope, resilience, optimism, and one’s ability to positively reframe a situation, all of which shape an individual’s responses to and management of challenges. The adolescence period is crucial to the development of Psychological capital (Psycap), and the extent to which it is cultivated will determine levels of happiness in one’s future. Its role within the unique socio-educational environment, however, is still unresolved in the context of Islamic boarding schools. Purpose: The objective of this research was to analyze the correlation of Psychological Capital (PsyCap) with the Subjective Well-Being (SWB) of youth in Indonesian Islamic boarding schools. Methods: Information was obtained through a cross-sectional survey distributed to 208 adolescents. The Psychological Capital Questionnaire was administered to gauge the PsyCap. The Satisfaction With Life Scale (SWLS), in conjunction with the Positive and Negative Affect Schedule (PANAS), was employed to measure subjective well-being (SWB). For data analysis, descriptive statistics and Pearson correlation were used. Results: This investigation determined that mean scores for all PsyCap components and SWB besides observed the clearly connected data that as PsyCap increased, SWB also appeared to elevate. Among components, hope demonstrated the strongest correlation (r = 0.444, p<0.001), followed by optimism (r = 0.407, p<0.001), efficacy (r = 0.364, p<0.001), and resilience (r = 0.363, p<0.001). Conclusion: All PsyCap components positively correlated with subjective well-being and with hope being the strongest predictor. This underscores the significance of hope-augmentation PsyCap interventions within the context of a boarding school to aid in the development and well-being of adolescents.